Intrinsic elements of the novel "Victor Frankenstein" - Adlina, Min; Muhammad, Pandy (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
This research explores the intrinsic elements of Mary Shelley's Victor Frankenstein, with a primary focus on the characterization of the dominant character. Utilizing a qualitative descriptive method, the study investigates how Victor Frankenstein's psychological and moral development shapes the narrative and reflects the novel's broader themes of ambition, isolation, and scientific responsibility. The analysis reveals that Victor is a complex, round character whose tragic downfall stems from a failure to assume responsibility for his creation. Additionally, the study examines the symbolic significance of the novel's settings, the narrative structure, and the ethical implications of unchecked scientific pursuit. By understanding these intrinsic elements, particularly characterization, readers can develop a deeper appreciation for the literary and philosophical dimensions of the novel. This research contributes to literary pedagogy by demonstrating how classical texts, such as Frankenstein, remain relevant in discussions about ethics, technology, and humanity.